Pesticide and Pathogen Exposure Causes Idiosyncratic Gene Expression Responses Across Four Diverse North American Bumble Bee Species - Rubén Martín‐Blázquez; Sydney A. Cameron; Austin C. Calhoun; James P. Strange; Ben M. Sadd (Molecular Ecology, 2025)
Bumble bee ( Bombus Latreille) populations of certain species have declined precipitously in North America over several decades. Hypotheses for declines include exposure to the pathogen Nosema bombi and neonicotinoid pesticides. Importantly, populations of some bumble bee species remain stable despite their presumed exposure to these same stressors. We hypothesise that declining and stable species exhibit distinct responses to N. bombi and neonicotinoids, detectable as differential gene expression profiles. To test this, we exposed larvae of Bombus occidentalis (declining) and B. impatiens (stable) to N. bombi and to the neonicotinoid imidacloprid, plus a combination of both. RNA‐seq analysis revealed almost no overlap between these species in gene expression responses to the individual stressors. There was more overlap of differentially expressed genes for the combined‐stressor condition, but hundreds of genes still showed species‐specific expression differences. To test whether the differential molecular responses could be associated with declining and stable species, we performed quantitative PCR on 20 selected genes, adding two additional species B. terricola (declining) and B. griseocollis (stable). These responses did not separate out by species decline status; each of the four species exhibit species‐specific responses. Overall, these results highlight that generalising mechanisms and causes of decline across different species may be misleading, as diverse species respond molecularly in a species‐specific manner to particular environmental stressors.